Current issues lembaga keuangan syariah - Huda, Nurul; Nasution, Mustafa Edwin (Rawamangun, Jakarta : Kencana : Ikatan Ahli Ekonomi Islam Indonesia, 2009)
Issues concerning Islamic financial institutions in Indonesia; papers.
Includes bibliographical references (p. 373-375).
Keywords: Financial institutions -- Indonesia -- Congresses; Islam -- Economic aspects -- Indonesia -- Congresses